THE GENERATION OF PLATE TECTONICS FROM MANTLE CONVECTION - Bercovici D. (My University, 2003)
In the last decade, significant progress has been made toward understanding how plate tectonics is generated from mantle dynamics. A primary goal of plate-generation studies has been the development of models that allow the top cold thermal boundary layer of mantle convection, i.e. the lithosphere, to develop broad and strong plate-like segments separated by narrow, weak and rapidly deforming boundaries; ideally, such models also permit significant strike-slip (toroidal) motion, passive ridges (i.e. pulled rather than pried apart), and self-consistent initiation of subduction. A major outcome of work so far is that nearly all aspects of plate generation require lithospheric rheologies and shear-localizing feedback mechanisms that are considerably more exotic than rheologies typically used in simple fluid-dynamical models of mantle flow. The search for plate-generating behavior has taken us through investigations of the effects of shear weakening ('stick-slip') and viscoplastic rheologies, of melting at ridges and low-viscosity asthenospheres, and of grain-size dependent rheologies and damage mechanics. Many such mechanisms, either by themselves or in combination, have led to self-consistent fluid-mechanical models of mantle flow that are remarkably plate-like, which is in itself a major accomplishment. However, many other important problems remain unsolved, such as subduction intiation and asymmetry, temporal evolution of plate geometry, rapid changes in plate motion, and the Archaean initiation of the plate-tectonic mode of convection. This paper presents a brief review of progress made in the plate-generation problem over the last decade, and discusses unresolved issues and future directions of research in this important area.
Keywords: MANTLE CONVECTION; PLATE TECTONICS